Parental Assistance Model in Online Learning for children Pandemic Period in Medan City - Lukitaningsih; Mhd Yusuf Nasution; Prihatin Ningsih Sagala (CV. Inara, 2021)
This study aims to find a pattern or model of mentoring carried out by parents during online learning for children during the pandemic in the city of Medan, and to describe the barriers to parents when mentoring online learning for their children. The method used is qualitative with a descriptive approach to see the activities that occur to parents during learning assistance during the pandemic. Data collection techniques were carried out by interviewing teachers, school children and parents, observations were carried out at home while children were studying. The sample of this study was in 5 sub-districts where each sub-district was taken 1 urban village with 1 teacher, 10 parents, 10 school children/urban village. The results of the study, namely the first pattern or model carried out by parents, there are four categories of models, namely 1) the inactive participation model category means that parents do not at all accompany their children to study, children study independently, or study groups of friends, children's initiative to learn is needed if there is any questions or materials that are not understood by children waiting and expecting the presence of the teacher when they come to visit which is done twice a month in study groups. 2). the category of active parent model means that parents actively supervise, motivate children to learn when doing assignments from the teacher according to the parents' free time, 3) quite active, meaning that parents accompany their children to learn online, ask the teacher for assignments if the child or other person parents do not understand the material, and help their children learn by using old mobile phones 4) very active, meaning parents lend and buy, facilitate their children's learning facilities such as cellphones to maximize learning, do their children's assignments at the office, send them to school and send assignments via WA in to the teacher. The results of the second study are the obstacles experienced by parents when assisting children in learning, namely not having time because parents work, do not master their children's subject matter, do not have internet facilities, cellphones due to economic factors.